Prevalance of Salmonella enterica in probiotics fed Giriraja and Sakini breed of chickens in Nepal - Neupane, D; Nepali, DB; Devkota, NR; Sharma, MP; Kadariya, IP (Progressive Agriculture, 2019)
Poultry industry has become an important economic activity in Nepal. But, due to awareness of consumers to antibiotic residue in the poultry meat and egg, there is increasing interest in finding alternatives to antibiotics for poultry production. The probiotics inhibit the growth of gastrointestinal pathogenic bacteria and also stimulate the immune response. The Salmonella enterica spp, a pathogenic bacterium that is responsible for low production and high mortality in poultry industry. This present study was undertaken to isolate and detect Salmonella enterica spp in probiotics fed Giriraja and Sakini breed of chickens. The experimental birds of each breed were divided into 4 groups (No probiotics, 5%, 10% and 15% probiotics) and each group was replicated four times. Prevalence of Salmonella in both probiotic treated and untreated groups were determined by culture and PCR using specific primers. In this study, Salmonella enterica spp isolated from the blood of different probiotics fed Giriraja and Sakini breed of Chickens were assessed for their prevalence in the poultry. The bacteria were isolated in the selective media and biochemically confirmed by the Bergey’s manual. One set of oligonucleotide primers, one of which is genus specific 16srRNA were employed for the molecular detection by the Polymerase Chain Reaction (PCR) assay. The amplified fragment in agarose gel electrophoresis as observed at 406bp confirmed the isolates to be Salmonella enterica spp. Of the 160 samples taken, 52 isolates (control) were confirmed to the bacteria of quest. The prevalence of Salmonella was zero in chickens with high (15%) concentration of Probiotics that reduced the growth of pathogens. Similarly, the prevalence rate was few in 10% concentration of probiotics and many in 5% and control. Progressive Agriculture 29 (4): 353-358, 2018